How I treat cancer: treatment of rheumatological side effects of immunotherapy - Gente, Karolina; Lorenz, Hanns-Martin; Leipe, Jan; Jordan, Karin (ESMO open, 2019)
Rheumatic immune-related adverse events (irAEs) have long been underestimated. However, arthralgia or myalgia are common side effects of immune checkpoint inhibitors (ICPi) reported in up to 10-20% of patients in clinical trials. Although rheumatic irAEs are rarely life-threatening, patients' quality of life can be considerably restricted due to pain, stiffness and limited mobility. Rheumatic irAEs can resemble known rheumatic and musculoskeletal diseases (RMDs), but often do not fulfil the classification criteria of classical entities and standardised evidence-based guidelines for their management are so far lacking. Herein, we discuss specific characteristics of rheumatic irAEs and present a comprehensible diagnostic and therapeutic approach to the management of these side effects. - - Rheumatic immune-related adverse events (irAEs) have long been underestimated owing to the fact that chronic musculoskeletal symptoms are frequent in the general population and even more in patients with cancer due to the pain and paraneoplastic symptoms caused by the disease and the frequently associated physical inactivity. Moreover, musculoskeletal pain is a common unspecific side effect of many drugs. Arthralgia or myalgia has been reported in up to 10-20% of patients treated with immune checkpoint inhibitors (ICPi) in clinical trials.1-3 A further aspect is that the Common Terminology Criteria for Adverse Events (CTCAE) grading system used by oncologist is not adapted to classify rheumatological side effects, and therefore, does not adequately reflect severity and complexity of these symptoms. In this regard, musculoskeletal events with substantial functional impact (eg, limiting instrumental activities of daily living) may be only a grade 2 event by the CTCAE system whereas they would be a grade 3 event in the Rheumatology Common Toxicity Criteria system.3 4 Although rheumatic irAEs can cause substantial pain, disability and high level of suffering, the current lack of awareness regarding these events in physicians results in under-reporting.1 Therefore, actively …
Gesehen am 16.03.2020